2003
DOI: 10.1359/jbmr.2003.18.2.190
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Tumor Metastasis to the Bone: Challenges and Opportunities

Abstract: In human cancers, bone is a common site for metastasis. It is well known that metastasis is the cause of morbidity and mortality in patients with cancer. Both breast and prostate carcinomas have a propensity to metastasize to bone. In general, metastatic breast cancers result in osteolytic lesions. On the other hand, prostate cancer metastases are osteoblastic and result in osteosclerosis. Thus, bone formation and bone resorption are at the crux of the cancer metastasis problem. For example, in the prostate, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
80
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 28 publications
0
80
0
1
Order By: Relevance
“…Of patients who died of PCa, the incidence of bone metastases at the autopsy examination was 65%-85%. 9 Bone metastases of PCa often occurs in rich blood supply sites, such as the vertebrae, pelvic bones, ribs, skull and proximal long bones, as well as other parts. 10 The low lumbar spine is the most common site of bone metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Of patients who died of PCa, the incidence of bone metastases at the autopsy examination was 65%-85%. 9 Bone metastases of PCa often occurs in rich blood supply sites, such as the vertebrae, pelvic bones, ribs, skull and proximal long bones, as well as other parts. 10 The low lumbar spine is the most common site of bone metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of bone lesions associated with breast cancer metastases are osteolytic (4)(5)(6)(7). It is thought that breast cancer cells secrete factors that act in a paracrine fashion to activate osteoclasts, leading to bone resorption.…”
Section: Introductionmentioning
confidence: 99%
“…Bone resorption is accompanied by release of growth factors and cytokines previously deposited within the matrix during bone formation. These growth factors act, in turn, back on the breast cancer cells to promote their further proliferation, establishing the ''vicious cycle'' of breast cancer skeletal metastasis (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Clinical and experimental evidence has shown that the tumor growth in bone microenvironment largely depends on the osteoclast activation induced by cytokines and growth factors released from neoplastic cells. [4][5][6][7][8] In the recent years, there have been major advances in understanding how osteoclastogenesis is regulated. [9][10][11] Two molecules, including ''receptor activator of NF-jB'' ligand (RANKL) and osteoprotegerin (OPG), play a fundamental role in controlling proliferation, differentiation, fusion, activation and apoptosis of osteoclasts.…”
mentioning
confidence: 99%